John Steinbeck in Poland. - Wieslaw Ksiazek:::Creator::::::::::::
John Steinbeck and Roels in the courtyard of the Collegium Maius (established 1400, 'Great College,' originally Akademia Krakowska), historical seat of Jagiellonian University in Poland. Original is in the safe.